MEASUREMENT OF SHARIAH-COMPLIANT HOTEL: A REVIEW - Fazil, Anis Hafiza; Saidin, Nurulaina; Fazil, Fauzunnasirah (Jurnal 'Ulwan, 2023)
Malaysia as one of the Muslim countries has set an exemplary standard of practice (SOP) for shariah-compliant businesses that has been recognized worldwide. Although discourse on the concept of halal practices in tourism and hospitality is proliferating, however evidence on the implementation of Shariah compliant practice for tourist accommodation sector remain scarce. Therefore, this study aims to present Shariah compliant measurement for hotels to apply Shariah compliant. Related document from previous studies were analysed to acquire the key attributes of Shariah compliant hotel (SCH) implementation. The findings indicated that the current scope of SCH practices include the areas of operations, design and interiors, and financial. In addition, a new concept for SCH has been introduced to complement the existing practices. The implications of this study were discussed from both academic and industry perspectives. This study enriches the existing knowledge on Shariah compliant concept specifically to tourist accommodation sector.